PENGARUH EARNING PER SHARE, DEBT TO EQUITY RATIO, DAN INFLATION RATE TERHADAP RETURN SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE - Ulfi Jefri; Rika Kartika; Lilis Istiqomah (LPPM Universitas Bina Bangsa, 2022)
The average stock return in 2017-2019 decreased and was followed by a decrease in the average Earning Per Share in 2016 and 2018. These results prove that changes in stock returns will be followed by changes in Earning Per Share in the same direction. Earnings Per Share with stock returns has a unidirectional relationship, therefore if you want to produce high stock returns, you need to pay attention to the Earning Per Share value. This study aims to analyze the partial and simultaneous effect of Per Share (EPS), Debt to Equity Ratio (DER) and Inflation Rate variables on stock returns in property and real estate sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. . The research method is quantitative with purposive sampling technique. The results of this study show that in property and real estate companies for the 2015-2019 period the Earning Per Share variable has an effect on Stock Return, while the Debt to Equity Ratio and Inflation Rate partially have no effect on Stock Return, , and simultaneously Earning Per Share (EPS). , Debt to Equity Ratio (DER) and Inflation Rate have a significant effect on stock returns